Resveratrol and SRT1720 Elicit Differential Effects in Metabolic Organs and Modulate Systemic Parameters Independently of Skeletal Muscle Peroxisome Proliferator-activated Receptor γ Co-activator 1α (PGC-1α) - Svensson, Kristoffer (American Society for Biochemistry and Molecular Biology, 2015)

(untitled) (J Biol Chem)
Resveratrol (RSV) and SRT1720 (SRT) elicit beneficial metabolic effects and are postulated to ameliorate obesity and related metabolic complications. The co-activator, peroxisome proliferator-activated receptor γ co-activator 1α (PGC-1α), has emerged as a major downstream effector responsible for metabolic remodeling of muscle and other metabolic tissues in response to RSV or SRT treatment. However, the requirement of PGC-1α in skeletal muscle for the systemic metabolic effects of these compounds has so far not been demonstrated. Using muscle-specific PGC-1α knock-out mice, we show that PGC-1α is necessary for transcriptional induction of mitochondrial genes in muscle with both RSV and SRT treatment. Surprisingly, the beneficial effects of SRT on glucose homeostasis and of both compounds on energy expenditure occur even in the absence of muscle PGC-1α. Moreover, RSV and SRT treatment elicit differential transcriptional effects on genes involved in lipid metabolism and mitochondrial biogenesis in liver and adipose tissue. These findings indicate that RSV and SRT do not induce analogous metabolic effects in vivo. Our results provide important insights into the mechanism, effects, and organ specificity of the caloric restriction mimetics RSV and SRT. These findings are important for the design of future therapeutic interventions aimed at ameliorating obesity and obesity-related metabolic dysfunction.